Preoperative Microbiomes and Intestinal Barrier Function Can Differentiate Prodromal Alzheimer’s Disease From Normal Neurocognition in Elderly Patients Scheduled to Undergo Orthopedic Surgery - Duan, Mei; Liu, Fangyan; Fu, Huiqun; Lu, Shibao; Wang, Tianlong (Frontiers in Cellular and Infection Microbiology, 2021)
Objective Emerging evidence links perturbations in the microbiome to neurodegeneration in amnestic mild cognitive impairment (aMCI) and Alzheimer’s disease (AD) and to surgical stress. In this study, we attempted to identify preoperative differences intestinal microbiota (IM) and barrier function between pAD [prodromal AD: Subjective cognitive decline (SCD) and aMCI] patients and normal neurocognition (NC) patients. Additionally, the potential associations between IM and barrier function, inflammation, and the clinical characteristics of pAD were evaluated. Design Eighty elderly patients scheduled to undergo orthopedic surgery were consecutively enrolled and grouped as NC, SCD, and aMCI following neuropsychological assessment. IM was determined by 16S rRNA MiSeq sequencing, and PICRUSt was used to predict functional shifts in IM. Furthermore, we investigated the association between IM and plasma claudin-1, occludin, LPS, systemic inflammatory cytokines, neuropsychological assessment, and clinical characteristics. Results There was a lower Chao1 index in the SCD group (P = 0.004) and differences in beta diversity among the three groups (PCA: P = 0.026, PCoA: P= 0.004). The relative abundance of Bacteroidetes was higher in the SCD group (P = 0.016, P = 0.008), and Firmicutes were more enriched in the aMCI group than in the SCD group (P= 0.026). At the family level, the total abundance of Gram-negative bacteria was higher in the SCD group than in the aMCI group (P = 0.047), and the Christensenellaceae family was detected at lower levels in the SCD and aMCI groups than in the NC group (P= 0.039). At the genus level, the eleven short-chain fatty acid (SCFA)-producing bacteria exhibited differences among the three groups. PICRUSt analysis showed that the pathways involved in SCFA catabolism, biosynthesis, and adherent junctions were reduced in SCD patients, and lipid synthesis proteins were reduced in pAD patients. Meanwhile, elevated plasma LPS and CRP were observed in SCD patients, and higher plasma occludin in aMCI patients. The IM was correlated with plasma claudin-1, LPS, inflammatory factors, neuropsychological assessment, and clinical characteristics. Conclusion The intestines of SCD and aMCI patients preoperatively exhibited IM dysbiosis and barrier dysfunction, and elevated plasma LPS and CRP were observed in SCD patients.